The Influence Of Educational Background And Ability To Write The Qur'an On Arabic Language Learning - Ahmad Zaki Yamani; Ahmad Muhammad Husni (Jurnal Al-Maqoyis, 2022)
This study aimed to examine the effect of students’ educational background on Arabic learning achievement, the effect of al-Qur'an literacy skills on student learning achievement and the effect of educational background and al-Qur'an literacy skills concurrently on Arabic learning achievement of Religious Department Students at MAN Kotabaru and MAN Tanah Bumbu.This study used a quantitative research with all Religious Department students at MAN Kotabaru (216 students) and MAN Tanah Bumbu (103 students) as the population. The sample contained 25% of each population which is 90 students: 60 students from MAN Kotabaru (30 students graduated from MTs and 30 students graduated from SMP) and 30 students from MAN Tanah Bumbu (15 students graduated from MTs and 15 students graduated from SMP). The data collection instruments were questionnaires, tests and documentation. The data analysis technique used simple regression analysis and multiple regression analysis.The results showed that there was an influence of educational background on Arabic learning achievement of Religious Department students by 28% at MAN Kotabaru and 30.9% at MAN Tanah Bumbu. Furthermore, there was an influence of al-Qur'an literacy skills on Arabic learning achievement of Religious Department students by 44% at MAN Kotabaru and 37% at MAN Tanah Bumbu. Further, there was an influence of educational background and the al-Qur'an literacy skills on the Arabic language learning achievement of Religious Department students by 52.1% at MAN Kotabaru and 46.9% at MAN Tanah Bumbu. It could be concluded that the Arabic language learning achievement of Religious Department students at the both of schools was influenced by other factors outside of this study.